Learning application for conversational Mandarin language / Nabihah Musa - Musa, Nabihah (2020)
Educational technology is has rapidly grown faster due to the cycle of time. Ideally, educational technology should be interactive and attractive for learning Mandarin language. The application development methodology employs the feasibility phase and Instructional Design Model by Alessi and Trollip. The application is to help the student to memorize and pronounce the words correctly using a multimedia approach. The Quasi experiment was done to measure its effectiveness in enhancing word recall and pronunciation in Mandarin language. The results indicate that multimedia approach can influence the performance of students since the results obtained by students more reliable and positive. It is shown that the Learning Conversational Mandarin Language application is effective for student in learning Mandarin language. It was found that by adapting these multimedia principles such as personalization principle, spatial contiguity principle and audio principle into the learning application, the word recall and pronunciation in Mandarin language among students could be enhanced.